"Thinking before posting?" Reducing cyber harassment on social networking sites through a reflective message. (January 2017) - Van Royen, Kathleen; Poels, Karolien; Vandebosch, Heidi; Adam, Philippe
Abstract: To deal with cyber harassment amongst youth on social networking sites (SNS), interfaces automatically showing a reflective message when harassment is recognized could be integrated. Such message encourages users to reconsider and to eventually self-censor their post. This study examines whether reflective messages reduce harassment among adolescents on SNS. We conducted an experimental study to test the effect of three different types of reflective messages, as well as a mere time delay, on the change in intention to engage in harassment on SNS. Participants were 321 adolescents from 15 to 16 years old (59.1% was female). We measured their intention to harass prior and after exposure to a reflective message. Moreover, we tested whether certain groups (based on their gender, empathy trait and behavioral inhibition) are more susceptible to certain types of reflective messages. The results show that, for all three conditions, the intention decreased after being exposed to the message, as well as following only a time delay. Furthermore, in one condition a stronger effect was found for individuals with a higher sensitivity of the behavioral inhibition system. Highlights: Reflective messages can reduce the adolescents' intention to harass on social media. Also a time delay is found effective in reducing the intention to harass. The user experience must be further optimized in future studies.